2002
DOI: 10.1021/jm0110892
|View full text |Cite
|
Sign up to set email alerts
|

Lepadins D−F:  Antiplasmodial and Antitrypanosomal Decahydroquinoline Derivatives from the Tropical Marine Tunicate Didemnum sp.

Abstract: From a new tunicate species, belonging to the genus Didemnum, three alkaloids possessing an unusual and extremely rare decahydroquinoline skeleton and showing significant and selective antiplasmodial and antitrypanosomal activity were obtained as follows: (2R*,3S*,4aR*,5R*,8aS*)-decahydro-3-hydroxy-5-(5'-hydroxyoctyl)-2-methylquinoline (lepadin D,1), its quaternary nitrogen derivative (2), (2R*,2"E,3S*,4aR*,5R*,8aS*)-decahydro-3-hydroxy-5-(5'-hydroxyoctyl)-2-methyl-3-quinolinyl ester 2"-octenoic acid (lepadin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 34 publications
4
72
0
Order By: Relevance
“…The structurally related but biologically different lepadins 1-8 (Fig. 1) are on the other hand marine alkaloids isolated from three distinct ascidians: Clavelina lepadiformis (found in the North Sea), Didemnum, and Aplidium tabascum (both found in the Great Barrier Reef) [2][3][4][5]. The third group consists of more complex polycyclic alkaloids that besides the DHQ ring system, can contain several other heterocyclic ring systems fused into one molecule.…”
Section: In This Review the Marine Derived Decahydroquinoline Alkaloimentioning
confidence: 99%
“…The structurally related but biologically different lepadins 1-8 (Fig. 1) are on the other hand marine alkaloids isolated from three distinct ascidians: Clavelina lepadiformis (found in the North Sea), Didemnum, and Aplidium tabascum (both found in the Great Barrier Reef) [2][3][4][5]. The third group consists of more complex polycyclic alkaloids that besides the DHQ ring system, can contain several other heterocyclic ring systems fused into one molecule.…”
Section: In This Review the Marine Derived Decahydroquinoline Alkaloimentioning
confidence: 99%
“…2 and ascidian Aplidium tabascum. 3 Structurally, all of them incorporate a methyl substituent at the C-2 position of the decahydroquinoline nucleus, a functionalized eight-carbon chain at C-5, and a free or acylated hydroxy group at C-3.…”
mentioning
confidence: 99%
“…4 Lepadins D-F have low cytotoxicity but significant and selective 25 antiplasmodial and antitrypanosomal activity. 2 Further pharmacological research on these alkaloids has been hampered by the low quantities of samples available from natural sources. This has stimulated considerable synthetic effort in this area, 5 although the development of facile enantioselective routes to 30 lepadins or synthetic analogs is still required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] These compounds have been found to possess significant in vitro cytotoxicity against several human cancer cell lines. [2] Very recently, Wright et al reported the isolation of lepadins D-F from a new Didemnum species collected from the Great Barrier Reef, [3] whereas Carroll and co-workers described their discovery of lepadins F-H in Aplidium tabascum Kott. [4] Interestingly, lepadins D-F showed low cytotoxicity but significant and selective antiplasmodinium and antitrypanosomal activity and therefore may serve as lead structures for the development of novel antimalarial drugs.…”
mentioning
confidence: 99%